Governance analysis in the Egadi Islands Marine Protected Area: A Mediterranean case study. (September 2016) - D'Anna, Giovanni; Fernández, Tomás Vega; Pipitone, Carlo; Garofalo, Germana; Badalamenti, Fabio
Abstract: The Egadi Islands Marine Protected Area (E-MPA), one of the largest MPAs in European seas, is a clear example of a complex protected area where multiple stakeholders such as administrative and political bodies, enforcement bodies, tourist operators and fishermen coexist in a legislative and management scenario characterized by overlapping and sometimes competing institutions and regulations. A governance analysis was carried out in April 2012. Semi-structured interviews were conducted amongst eight stakeholder groups in order to understand their perspectives on the governance of the E-MPA and to collect their views about the main MPA issues. Overall the E-MPA is perceived as a top-down initiative imposed by politicians without any involvement of the local population. Three categories of conflicts were identified: fisheries vs. conservation, tourism vs. conservation and fisheries vs. tourism. Tourist excursions with large boats are considered among the most impacting activities on the environment as well as on small boat renters. Inside the fishing sector strong conflicts occur between artisanal fishing and illegal inshore trawling, and also between artisanal fishers and recreational fishers who illegally sell their catch. The MPA management has been weak and inefficient until 2010, when the new MPA director imparted a new direction to the management based on greater transparency and participation. More incentives and a wider participation of stakeholders are deemed essential to a more effective management of the MPA. Highlights: Governance analysis run in a very large Italian marine protected area. Conflicts: fisheries vs conservation, tourism vs conservation, fisheries vs tourism. MPA perceived by stakeholders as a result of a top-down process. Weak management regardless of local population opinion. Better participation and transparency since new MPA management in 2010.